Study of deformation of the head stack assembly (has) during de-swage process - Boonsri, Santiti; Tangchaichit, Kiatfa (Asia-Pacific Journal of Science and Technology, 2017)
In a conventional hard disk drive assembly process, swaging process is used for attaching a suspension arm which has a read/write head at its tip, to an actuator arm. Deswaging is a process of disconnecting those components that have been joined by swaging. When a suspension has a defective read/write head, it is required to de-swage the suspension arm from the actuator arm and replace with a new good suspension arm. During a de-waging process, the blade of a de-swage tool is made to slide on a surface for disconnecting an actuator arm and a suspension arm by applied force. Apply force have an effect on deformation of the actuator arm. This work aims to study the deformation of an actuator arm during de-swaging process by using finite element analysis. The results showed that the optimum applied force of a de-swage tool, which result in minimum gram load, is 5 N.